Analysis of the complete mitochondrial genome of Vietnamese Pygathrix nigripes - Nguyen, Thi Thuy Tram; Le, Thanh Long; Ho, Nguyen Quynh Chi; Phan, Luu Chinh Nhan; Ha, Thanh Tung; Dang, Thi Tung Loan; Nguyen, Thi Phuong Mai (Vietnam Journal of Biotechnology, 2025)
The black-shanked douc langur Pygathrix nigripes is a critically endangered primate species endemic to Vietnam, facing severe threats from habitat destruction, poaching, and climate change. This study presents the complete mitochondrial genome of Pygathrix nigripes, comprising 16,535 bp, which includes 37 genes: 13 protein-coding genes, 22 transfer RNAs, and 2 ribosomal RNAs. Mitochondrial genomes are crucial for cellular energy metabolism, and understanding their genetic structure is vital for effective conservation strategies. Our analysis reveals significant genetic diversity and an A-T rich nucleotide composition, characteristic of primate mitogenomes, indicating adaptive evolutionary strategies. The study also highlights the importance of mitochondrial protein-coding genes in energy production and metabolic efficiency, which are critical for the species' survival. We observed variations in nucleotide composition and codon usage bias that reflect historical population dynamics and evolutionary pressures. Comparative genomic analyses with other Pygathrix species suggest shared evolutionary pathways, emphasizing the need for targeted conservation efforts. The findings underscore the necessity of genetic monitoring in conservation planning, particularly as Pygathrix nigripe faces ongoing environmental challenges. This research aims to enhance the global mapping of the Pygathrix nigripes mitogenome, offering valuable insights that can support the development of effective conservation strategies. These strategies are essential for ensuring the survival of this unique and critically endangered primate species.